Anxiety dalam Karya Seni Grafis Stencil Print - Farras Hamzani; Ariusmedi Ariusmedi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The rise of Anxiety among adolescents to adults greatly affects their daily activities. Anxiety is a natural emotional response to pressure or situations that are perceived as threatening. This work aims to visualize the condition of anxiety as a form of mental illness that is often ignored, especially among teenagers and adults. Using stencil print graphic art technique, this work tries to express the symptoms of anxiety through visual symbols, such as facial expressions and objects that support the impression. The process of creating this work involves in-depth observation and literature review to enrich the understanding of the concept of anxiety. The author hopes that through this work, people can better understand the complexity and impact of anxiety, and the importance of maintaining mental health. This work is also expected to be a learning tool for the public in understanding mental issues.